Separation of aromatic and aliphatic hydrocarbons using deep eutectic solvents: A critical review - Hadj-Kali, M.K.; Salleh, Z.; Ali, E.; Khan, R.; Hashim, M.A. (Elsevier, 2017)
The reported experimental data for the separation of aromatic from aliphatic compounds using green solvents is growing exponentially. This paper surveys the existing data and presents a critical review that helps clarifying the major findings, identifies shortcomings and provides some recommendations. The comparison between deep eutectic solvents (DESs) and both ionic liquids (ILs) and classical organic solvents for this challenging separation is also presented based on experimental selectivity and distribution ratio data. This comparison confirms the capability of DESs to effectively extract aromatic compounds and shows that DESs can compete with ILs and even outclass them in some cases. Moreover, our comprehensive literature survey has revealed that in many cases the use of DESs yields to a minimum cross-contamination between the two phases. This will undeniably facilitate the separation procedure and thus reduce the cost of the separation process. On the other hand, the performance of COSMO-RS to predict ternary liquid-liquid equilibrium diagrams for systems including DESs is also evaluated in this work for all available data. COSMO-RS was able to reproduce the experimental tie-lines with a good accuracy in many cases. Therefore, it represents a cost-effective and time-saving screening tool to evaluate the extraction performance of the unlimited number of possible salt/complexing agents' combinations.